Low-temperature structural phase transitions of the lead-free hybrid vacancy-ordered perovskite (DMA)2SnBr6 - Furtado, Otávio Peixoto (2023)
In this master’s thesis, a combination of experimental and theoretical techniques are employed to investigate the hybrid vacancy-ordered perovskite material [(CH3)2NH2]2SnBr6 (or in its abbreviated form: (DMA)2SnBr6) and its structural changes that happen at low temperatures. Through the use of experimental techniques such as Single Crystal X-Ray Diffraction (SCXRD), Differential Scanning Calorimetry (DSC) and Raman spectroscopy, it was possible to identify that this compound undergoes three structural phase transitions near the temperatures of 200 K, 100 K and 50 K. The first two transitions were found in our SCXRD measurements, with the first one being a displacive orthorhombic-monoclinic phase transition, while the second one was found to be an order-disorder monoclinic-triclinic phase transition. The last transition was only observed experimentaly through our Raman spectroscopy measurements and was confirmed as a triclinic-triclinic phase transition based on our theoretical Γ-point phonon calculation.